Improvement of Valgus Deviation of the Lesser Toes of Moderate to Severe Hallux Valgus After Proximal Chevron Metatarsal Osteotomy and Akin Osteotomy - Hong-Geun Jung MD, PhD (Foot & Ankle Orthopaedics, 2018)
Category: Lesser Toes Introduction/Purpose: The valgus deviation of lesser toes is often found in the hallux valgus patients. It has been known that valgus deviation of lesser toes remain unchanged even after correction of hallux valgus. The purpose of this study was to determine whether valgus deviation of lesser toes can be corrected after proximal chevron metatarsal osteotomy (PCMO) and Akin osteotomy for the hallux valgus patients, and to evaluate the factors affecting the degree of correction. Methods: The study is based on 116 feet (89 patients) of moderate to severe hallux valgus that underwent proximal chevron metatarsal osteotomy with Akin ostetomy. Hallux valgus angle (HVA), inter-metatarsal angle (IMA), valgus angle of 2nd, 3 rd, 4th metatarso-phalangeal joint were assessed preoperatively and postoperative 6 month, 1 year and yearly. VAS pain cores, American Orthopedic Foot and Ankle Society metatarsophalangeal-interphalangeal (AOFAS MTP-IP) scale and patient satisfaction were evaluated preoperatively and at subsequent follow-up. Results: The average follow-up was 30.6 months (range,12-99). The mean HVA and IMA reduced from 34.4° to 8.7° and 15.9° to 5.3° respectively at the final follow-up. Patients with more severe HVA showed higher degree of valgus deviation of lesser toes than those with lesser HVA. The valgus angle of 2nd,3 rd,4th MTP joints reduced from 8.9°, 6.7°, 2.4° preoperatively to 5.6°, 4.9°, 1.3° respectively at the final follow-up (p<0.05). The more HVA corrected, the more valgus deviation of lesser toe was found corrected. There was no significant difference in the degree of lesser toe correction angle according to follow up period after postoperative 1 year. The mean VAS and AOFAS scores significantly improved from 6.0, 60.9 to 1.2, 92.0 at the final follow-up, respectively (P<0.05). Conclusion: Unlike the previous reports, the current study showed significant reduction of the valgus angle of 2nd, 3 rd, 4th MTP joints after PCMO and Akin osteotomy for the moderate to severe HV without additional corrective lesser toe surgery.